RETRACTED: Sustainable development features of the socio-ecological economic system - Bikmetov Evgeniy; Lukyanov Arkadiy; Pushkareva Marina; Sizonenko Zarina; Khramova Ksenia (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001